WHIPPLE RESECTION: CONCORDANCE BETWEEN FROZEN SECTION AND PERMANENT SECTION DIAGNOSIS OF SURGICAL MARGINS - Bilal, Muhammad; Tariq, Hina; Mamoon, Nadira (Journal of Ayub Medical College Abbottabad, 2018)
Background: Margin assessment is done in Whipple procedures which are usually performed to resect tumours of head of pancreas and ampullary/periampullary region. Aims and objective of the study are to determine the concordance between frozen sections (FS) and permanent sections (PS) of surgical margins in Whipple resections. Methods: It is a retrospective study, from January 2008 to January 2015 (07 years). It includes the specimen with malignancy in final report and for which FS of pancreatic and/or CBD margin(s) were requested. Data was retrieved from Laboratory information system (LIS) database. Results: Of the 41 bile duct margins in cases of ampullary tumours, 03 were positive on FS as well as PS, 35 were negative on FS as well as on PS. Results showed 100% sensitivity, 92.1% specificity, 50% PPV and 100% NPV. Results of 36 pancreatic margins in cases of ampullary showed 100% sensitivity, 97.1% specificity, 50% PPV and 100% NPV. In pancreatic carcinoma cases, none of CBD margins were reported as positive on FS, 02 margins reported as negative were found positive on PS, while 17 were negative on FS as well as PS. Results showed 100% specificity and 89.5% NPV. Of the 27 pancreatic margins tested in pancreatic tumours 100% sensitivity, 94.1% specificity, 88.9% PPV and 100% NPV was found. Conclusion: Factors such as absent prior tissue diagnosis and/or inflammatory processes make margin diagnosis difficult. However, a high concordance was observed between our FS and PS diagnosis. Keywords: Frozen section; Pancreatic carcinoma; Pancreatic duct